“I give up and stop listening”: Fostering metacognitive listening strategy awareness in the English classrooms in Taiwan - Chen, Chiung-chiuen; Tseng, David S. D. (Advances in Social Sciences Research Journal, 2017)
This study aims to investigate the instructional effect of metacognitive listening strategies on EFL college students’ metacognitive listening strategy awareness as well as their perceptions of strategy instruction. This study uses a process-based approach for instruction of metacognitive strategies. The instruments in this study include a metacognitive awareness listening questionnaire (MALQ) and a stimulated-recall on MALQ. The results show that there is slightly positive effect of instruction though there is no statistically significant effect of listening strategy instruction on student’s metacognitive listening strategy awareness. Plus, surprisingly, it is found that students are conscious of their metacognitive strategy use as they listen. It is suggested that teachers use various authentic listening text for fostering EFL college students’ metacognitive listening strategy awareness.